Claustral Input to the Macaque Medial Posterior Parietal Cortex (Superior Parietal Lobule and Adjacent Areas). (3rd May 2021) - Gamberini, Michela; Passarelli, Lauretta; Impieri, Daniele; Montanari, Giulia; Diomedi, Stefano; Worthy, Katrina H; Burman, Kathleen J; Reser, David H; Fattori, Patrizia; Galletti, Claudio; Bakola, Sophia; Rosa, Marcello G P
Abstract: The projections from the claustrum to cortical areas within and adjacent to the superior parietal lobule were studied in 10 macaque monkeys, using retrograde tracers, computerized reconstructions, and quantitative methods. In contrast with the classical view that posterior parietal areas receive afferents primarily from the dorsal and posterior regions of the claustrum, we found that these areas receive more extensive projections, including substantial afferents from the anterior and ventral regions of the claustrum. Moreover, our findings uncover a previously unsuspected variability in the precise regions of the claustrum that originate the projections, according to the target areas. For example, areas dominated by somatosensory inputs for control of body movements tend to receive most afferents from the dorsal-posterior claustrum, whereas those which also receive significant visual inputs tend to receive more afferents from the ventral claustrum. In addition, different areas within these broadly defined groups differ in terms of quantitative emphasis in the origin of projections. Overall, these results argue against a simple model whereby adjacency in the cortex determines adjacency in the sectors of claustral origin of projections and indicate that subnetworks defined by commonality of function may be an important factor in defining claustrocortical topography.